AN EMPIRICAL STUDY OF THE CONTRIBUTIONS OF ROTATING SAVINGS AND CREDIT ASSOCIATIONS (ROSCAS) TO ECONOMIC DEVELOPMENT OF ILORIN METROPOLIS - Abdul-Yakeen, Mufutau Ayinla (European Scientific Journal, ESJ, 2012)
The Empirical Study of The Contributions of Rotating Savings and Credit Associations (ROSCAS) to The Economic Development of Ilorin Metropolis, capital of Kwara State of Nigeria, was informed by the fact that CBN/NDIC (1995) confirmed that there was distress in the Nigerian financial industry; Besley, et al (1994) observed that there was little focus of economists on the activities of ROSCAS; and Ijaiya (2002) suggested that there should be further studies conducted on the informal financial institutions in Ilorin Metropolis. So the researcher obtained primary data to analyze the views of four hundred respondents who were ROSCAS members in the study area. Data was analyzed using descriptive and inferential models of data analysis. After using E-View 3 software package to run the regression analysis, the hypotheses tested were to know the relationship between the years of employment of respondents and the number of ROSCAS they have joined; their savings and income relationship; and the relationship between the items bought with loans obtained from ROSCAS. Students‟ t-test was conducted on the first two hypothesis while f-statistic was employed on the last hypothesis. The results of the tests did not conform with the priori assumptions. It was discovered that respondents were likely to join ROSCAS even if they do not earn income, contribute about thirty percent of their incomes to ROSCAS and this showed that savings to the purse of ROSCAS are not idle but active funds which could lead to an instantaneous multiplier effect of over one hundred and forty growth of the economy. As such ROSCAS‟ membership did promote cordial relationship between the lenders and the borrowers, employment generation, increase in output, consumption, savings, investment, and price stability because interest charges were absent in their dealings. It was recommended that individual persons, households, firms and governments should do everything possible to promote ROSCAS by prompt payment of dues, organization of ROSCAS, ensure that ROSCAS were available, and promulgate ROSCAS‟ laws respectively. Finally, the study of Keynesian, Simple Multiplier shall be extended to the savings of people to ROSCAS.